Optimal Gradual Annuitization: Quantifying the Costs of Switching to Annuities - Wolfram J. Horneff; Raimond H. Maurer; Michael Z. Stamos (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2007)
We compute the optimal dynamic asset allocation policy for a retiree with Epstein-Zin utility. The retiree can decide how much he consumes and how much he invests in stocks, bonds, and annuities. Pricing the annuities we account for asymmetric mortality beliefs and administration expenses. We show that the retiree does not purchase annuities only once but rather several times during retirement (gradual annuitization). We analyze the case in which the retiree is restricted to buy annuities only once and has to perform a (complete or partial) switching strategy. This restriction reduces both the utility and the demand for annuities.
Keywords: D91; G11; G22; J26; H55; 330; Portfolio Choice; Dynamic Asset Allocation; Insurance; Annuities; Pensions; Retirement; Retirement Policies; Rentner; Anlageverhalten; Portfolio-Management; Lebensversicherung; Zeitpräferenz; Theorie